2020
DOI: 10.1097/md.0000000000021697
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a critical thinking intervention on stress management among undergraduates of adult education and extramural studies programs

Abstract: Objective: The objective of this study was to examine the effect of a critical thinking intervention (CTI) on stress management among undergraduates of adult education and extramural studies programs. Method: A total of 44 undergraduates were randomly sorted into experimental and waitlist control groups. We used the Perceived Stress Scale for data collection at the pre-test, post-test, and follow-up stages. We used unpaired t and paired … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 13 publications
(18 reference statements)
1
15
0
Order By: Relevance
“…Critical thinking might help to reduce stress levels because it allows individuals to reflect about question stress-inducing stimuli, as well as to reinterpret the experience of uncertainty by identifying the reasons why an individual might feel stressed (Escolà-Gascón et al, 2021). In addition, a few intervention studies have found that training critical thinking helps to ameliorate stress (Okide et al, 2020;Ugwuozor et al, 2021). Nonetheless, the aforementioned studies have not been conducted on adolescent samples.…”
Section: Discussionmentioning
confidence: 99%
“…Critical thinking might help to reduce stress levels because it allows individuals to reflect about question stress-inducing stimuli, as well as to reinterpret the experience of uncertainty by identifying the reasons why an individual might feel stressed (Escolà-Gascón et al, 2021). In addition, a few intervention studies have found that training critical thinking helps to ameliorate stress (Okide et al, 2020;Ugwuozor et al, 2021). Nonetheless, the aforementioned studies have not been conducted on adolescent samples.…”
Section: Discussionmentioning
confidence: 99%
“…High PSS-10 scores indicate a high level of stress. [ 28 , 29 ] Scores of 0 to 13 depict low stress, 14 to 26 depict moderate stress, and 27 to 40 depict high perceived stress. [ 28 , 29 ] The PSS-10 is suitable to be used among university students since it was found to have good internal consistency and construct validity, [ 30 ] as well as convergent validity.…”
Section: Methodsmentioning
confidence: 99%
“…[ 28 , 29 ] Scores of 0 to 13 depict low stress, 14 to 26 depict moderate stress, and 27 to 40 depict high perceived stress. [ 28 , 29 ] The PSS-10 is suitable to be used among university students since it was found to have good internal consistency and construct validity, [ 30 ] as well as convergent validity. [ 31 ] The present study found a Cronbach’s α score of.84 for the internal consistency reliability.…”
Section: Methodsmentioning
confidence: 99%
“…RCT sought to measure and compare the outcomes after the participants receive the interventions. This study design has been used by Nwokeoma et al, [ 8 ] Ogbuanya et al, [ 24 , 25 ] Garfield, [ 26 ] Ugwuanyi et al, [ 36 , 37 , 40 , 42 ] Ede et al, [ 38 ] Agboeze et al, [ 39 ] Okide et al, [ 41 ] Abiogu et al, [ 43 ] and Umoke et al [ 44 ] to carry out similar studies.…”
Section: Methodsmentioning
confidence: 99%